PENGARUH KOMISARIS INDEPENDEN, FREKUENSI RAPAT DEWAN KOMISARIS, REPUTASI AUDITOR, KOMPLEKSITAS, KEPEMILIKAN ASING, DAN UKURAN PERUSAHAAN TERHADAP KEBERADAAN RISK MANAGEMENT COMMITTEE (RMC) PADA PERUSAHAAN GO PUBLIC DI INDONESIA - Vina Wijayanti Hadi (Jurnal Akuntansi Bisnis, 2015)
This study aims to look at the influence of variable independent commissioner, the frequency of board meetings, the auditor's reputation, complexity, foreign ownership and size of enterprises to the existence of the risk management committee at the company went public in Indonesia. This research is expected to be input for the company in improving the implementation of good corporate governance practices, particularly in terms of risk management by establishing a Risk Management Committee or the Risk Management Committee. These observations were made by using secondary data. Secondary data used are annual reports of non-financial companies listed on the Stock Exchange. Logistic regression method selected for this study using non-metric variables as the dependent variable. While the independent variable is the variable metric and non-metric. There are several stages of testing done in analyzing the data in this study. Data analysis stage of research include analysis Descriptive Statistics, Regression Model Feasibility, Feasibility Overall Model, Coefficient of Determination, Matrix Classification and Regression Coefficients Test. Based on the research results can be concluded that the proportion of independent commissioners, auditor's reputation, and the complexity of the company do not affect the existence of the risk management committee. Instead, the frequency of board meetings, foreign ownership and firm size affects the existence of the risk management committee at the company went public in Indonesia.